Industrial design practice using rapid prototyping : a case study / Ahmad Zuhairi Abdul Majid - Abdul Majid, Ahmad Zuhairi (2005)
The production of a prototype is a critical step in any production and design process. Prototypes are necessary for determining tooling considerations, aesthetic evaluations, and design verification. In the past, prototype parts required weeks, even months, of high-cost machil1ing, hand modeling, and manual drawings and layouts. With the new technology of Rapid· prototyping (RP) provide solution in competitiveness. Rapid prototyping, in its generic sense, should be referred to as manufacturing processes that can- create prototype parts rapidly. The purpose of this research is to documenting a case study on product development that uses rapid prototyping service. From.this study also the researcher need to see the involvement of industrial designer in the development process in producing prototypes which required by the client, Tellinx Sejagat Sdn. Bhd. There are two main research questions to be. answered in the case study. One is to establish how that RI? could contribute towards enriching the design process in industrial design activities locally and to find what are the challenges that emerge when local industrial designer applies RP in the industrial design process. The case study identifies the significance ofrapid prototyping in industrial design in Malaysia. If RP is needed in the local industry, the analysis on the involvement of industrial designers in RP will reflect how the local industrial education could contribute.